The effectiveness of Melaleuca “Tea Tree” essential oil in the treatment of chronic wounds (Research, Society and Development, 2025)
Objective: To analyze, based on scientific literature, the therapeutic potential and application methods of Melaleuca alternifolia (Tea Tree) essential oil in the healing of chronic wounds. Method: This study is an Integrative Literature Review, conducted through a search of indexed databases available in the Virtual Health Library (VHL), covering the period from 2014 to August 2024. Results: A total of 119 articles were identified, of which 5 met the inclusion criteria. The selected studies demonstrated that Tea Tree essential oil, at concentrations of 5% to 10%, was effective in eliminating methicillin-resistant Staphylococcus aureus (MRSA) from the skin and significantly contributed to chronic wound healing. Additionally, analgesic, anti-inflammatory, and odor-reducing properties were observed, positively impacting patients' quality of life. In some cases, the combination with silver-based compounds showed synergistic potential in reducing microbial load. Conclusion: The evidence suggests that Melaleuca alternifolia essential oil has promising properties for the treatment of chronic wounds, particularly in managing MRSA infections and promoting tissue repair. However, the current body of literature is limited, highlighting the need for further well-designed clinical studies with larger sample sizes to validate its efficacy and safety.